Chloramine-T Assisted Oxidative Decolourization of Tartrazine (Food Dye) in Acid Medium: Kinetic and Mechanistic Investigations - Muddegowda, Harsha; Chandrashekar, Charan Kumar Hunsur; Narasigowda, Kumara Manikyanahalli (Trends in Sciences, 2022)
Tartrazine (TAZ) is a food color additive. It has been found to be contaminated with Benzidine or other carcinogens. It causes hypersensitivity reactions. The metabolites which are formed during digestion are responsible for the problems caused by these dyes. So, in the present work the kinetic and mechanistic aspects of oxidation of tartrazine have been studied with the help of mild oxidizing agent chloramine-T (CAT) in acid medium at 26 °C. The reaction exhibited 2nd-order dependence of rate with (CAT), inverse fractional order dependence of rate with (TAZ) and (H+). Solvent composition shows negative effect indicating the involvement of negative ion-dipolar molecule in the rate determining step. Variation of ionic strength of the medium and addition of halide ions had no effect on the reaction rate. Addition of p-toluenesulphonamide (PTS), the reduction product retards the rate of reaction. Oxidation products were identified as 4-(5-Hydroxy-4-nitoso-pyrazol-1-yl)- benzenesulphonic acid and 4-amino-benzene sulphonic acid which are often allergic to human beings. These oxidation products were characterized by LC-MS. Activation parameters have been evaluated from Arrhenius-Eyring plots. The observed results have been explained by plausible mechanism and related rate law have been deduced. HIGHLIGHTS The kinetics of oxidation of Tartrazine has been studied in acid medium by using CAT as an oxidizing agent Effects of different parameters like ionic strength, addition of reduction product, halide ions and temperature were studied as supporting data for the mechanism proposed for the oxidation of Tartrazine Products were isolated after complete oxidation and were characterized with the help of suitable technique A rate equation is derived and a suitable mechanism is proposed for the oxidation of the substrate GRAPHICAL ABSTRACT